FAKTOR PENYEBAB DAN DAMPAK DIGITAL WELL-BEING PADA SISWA REMAJA: SYSTEMATIC LITERATURE REVIEW - Fuad Fadil; Suhadianto Suhadianto; IGAA Noviekayati (STAI Sangatta Kutai Timur, 2026)
Digital well-being has become a crucial issue affecting the lives of adolescent participants in the cyber era. Excessive technology use significantly impacts psychological, academic, and physical stability; however, comprehensive syntheses regarding trends, causal determinants, and specific impacts remain limited. The findings of this review are expected to provide profound insights and strategic recommendations for achieving optimal digital well-being among the youth. Utilizing the Systematic Literature Review (SLR) method guided by the PRISMA 2020 framework, literature searches were conducted across Crossref, Scopus, and Google Scholar databases using Publish or Perish software. Out of 2,186 initial records, 50 studies (published 2020–2026) met the inclusion criteria and were extracted using thematic analysis. The synthesis reveals that digital well-being is shaped by four primary determinants: internal factors (self-control, emotion regulation), family (digital parenting), socio-interpersonal factors (peer norms), and environmental-contextual factors (digital learning). Management failure triggers serious consequences across psychological, academic-motivational, socio-behavioral, and physiological dimensions. Meanwhile, research trends indicate a shift in focus from mere screen time to the effectiveness of systemic interventions. These findings underscore the urgency of holistic educational policies that synergize families and schools to protect the mental health of adolescent participants.